2018
DOI: 10.3390/brainsci8090175
|View full text |Cite
|
Sign up to set email alerts
|

The Loss of α- and β-Tubulin Proteins Are a Pathological Hallmark of Chronic Alcohol Consumption and Natural Brain Ageing

Abstract: Repetitive excessive alcohol intoxication leads to neuronal damage and brain shrinkage. We examined cytoskeletal protein expression in human post-mortem tissue from Brodmann’s area 9 of the prefrontal cortex (PFC). Brain samples from 44 individuals were divided into equal groups of 11 control, 11 alcoholic, 11 non-alcoholic suicides, and 11 suicide alcoholics matched for age, sex, and post-mortem delay. Tissue from alcoholic cohorts displayed significantly reduced expression of α- and β-tubulins, and increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 75 publications
1
12
1
Order By: Relevance
“…MAP-2 is required for dendrite elongation [25]. It was reported that companied with the brain volumetric losses for alcoholic patients and the elderly, microtubule-associated proteins including MAP-2 and MAP-tau were also reduced [26]. Then we can deduce that expression of MAP-2 reflect the rough number of neurons.…”
Section: Discussionmentioning
confidence: 88%
“…MAP-2 is required for dendrite elongation [25]. It was reported that companied with the brain volumetric losses for alcoholic patients and the elderly, microtubule-associated proteins including MAP-2 and MAP-tau were also reduced [26]. Then we can deduce that expression of MAP-2 reflect the rough number of neurons.…”
Section: Discussionmentioning
confidence: 88%
“…In order to gauge if truncation of Tau could be detected in human brains, three different Tau antibodies were used to target epitopes in the middle, the N-terminus, or the C-terminus of the six Tau isoforms present in the human brain ( Figure 1 ). These antibodies have been used in a number of other Tau investigations, e.g., [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results of this study need to be interpreted in the light of the following caveats. Although the three antibodies that were used have been employed in many other published experiments on Tau, e.g., [ 32 , 33 , 34 , 35 , 36 ], we did not independently validate them. Since this was not intended to be a quantitative study, loading controls were not incorporated.…”
Section: Resultsmentioning
confidence: 99%
“…Tubulinopathies are characterized by various clinical features and are accompanied by a broad spectrum of malformations of cerebral cortices and subcortical structures, including the corpus callosum, the brainstem, and the basal ganglia [ 41 ]. Loss of α-tubulin and β-tubulin is a hallmark of chronic alcohol consumption and natural brain aging [ 42 ]. Along with these reports, our observations trigger the question of whether accelerated age-dependent loss of these cilia tubulins may contribute to the pathophysiological mechanisms of tubulinopathies.…”
Section: Discussionmentioning
confidence: 99%